A novel strategy for resource utilization of oily drilling waste fluids in northern Shaanxi: Stepwise flotation of bentonite and barite using SDS and interfacial reaction mechanisms - Liu Lihu; Shi Jiahe (PLoS ONE, 2025)
Northern Shaanxi’s oil-gas drilling produces large amounts of waste drilling fluids with high-value solids (barite, bentonite). Traditional disposal causes resource waste and pollution. This study proposes a stepwise flotation process for typical local oil-based waste: surface cleaning to break oil film wrapping and combined reagents to regulate mineral surface hydrophobicity differences, enabling efficient separation and recovery of barite and bentonite. The flotation mechanism is also preliminarily explored. The experimental results show that: ultrasonic cleaning with 0.5% sodium dodecyl sulfate (SDS) solution makes the oil desorption rate of solid phase >95%, restoring the natural surface properties of minerals. Through the stepwise flotation design, in the first stage at pH = 4.0, 0.8 kg/t sodium dodecyl sulfate and 0.6 kg/t sodium hexametaphosphate are added, and the recovery rate of bentonite reaches 86.3%; in the second stage at pH = 8.0, 1.2 kg/t sodium dodecyl sulfate and 0.7 kg/t gellan gum are added, and the grade of barite concentrate is 92.1% (BaSO₄ content), with a recovery rate of 88.7%. Through the flotation closed-circuit experiment, using the process of “one roughing, two cleaning and three scavenging”, the first stage can obtain bentonite concentrate with a recovery rate of 91.4% and a grade of 91.5%; the second stage can obtain barite concentrate with a recovery rate of 90.2% and a grade of 92.1%. SEM shows that bentonite is dissociated lamella, and barite presents clean prismatic crystals without oil film impurities, verifying the high efficiency of separation. Mechanism studies show that SDS has dual functions of oil breaking and collecting. Sodium hexametaphosphate inhibits the flotation of barite by chelating Ba²⁺ in barite. Gellan gum realizes separation by shielding the active sites of bentonite through hydrogen bonds. This study provides an efficient and low-consumption solution for the resource utilization of drilling waste liquid in northern Shaanxi.